2023
DOI: 10.1051/0004-6361/202245236
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of high-mass X-ray binaries in the Galaxy: from the INTEGRAL to the Gaia era

Abstract: Context. High-mass X-ray binaries (HMXBs) are a particular class of high-energy sources that require multi-wavelength observational efforts to be properly characterised. New identifications and the refinement of previous measurements are regularly published in the literature by independent teams of researchers and might, when they are collected in a catalogue, offer a tool for facilitating further studies of HMXBs. Aims. We update previous instances of HMXB catalogues in the Galaxy and provide the community ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 348 publications
0
29
0
Order By: Relevance
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…A handful of sources which are included in the recently published catalogue of high-mass X-ray binaries by Fortin et al (2023) are missing in our catalogue.Those are the already mentioned Sources AX J1700.1-4157, SAX J1819.3-2525 and AX J1838.0-0655, as well as GRS 1758-258. In the case of GRS 1758-258, there is a possibility that the system is a intermediate-mass X-ray binary as stated by Martí et al (2016), hence this source can be found in Avakyan et al (2023) instead of this catalogue.…”
Section: Finding Charts and Problematic Casesmentioning
confidence: 99%
“…can be found in the recently published catalogue of high-mass X-ray binaries in the Galaxy byFortin et al (2023) 26 https://alasky.u-strasbg.fr/hips-image-services/hips2fits…”
mentioning
confidence: 99%
“…The Corbet diagram (spin period 𝑃 spin vs. orbital period 𝑃 orb ) has been used as a great tool for studying the formation,evolution and accretion history of NS HMXB (Corbet 1984). We used the most updated HMXB catalog (Fortin et al 2023) and our NS LMXB samples to build the Corbet diagram. Our NS LMXB sample obviously differs from the HMXB sample on the Corbet diagram (see Figure 7).…”
Section: Ns Lmxbmentioning
confidence: 99%